Chemical Characteristics of Platycodon grandiflorum and its Mechanism in Lung Cancer Treatment - Deng, Yaling; Ye, Xianwen; Chen, Yufan; Ren, Hongmin; Xia, Lanting; Liu, Ying; Liu, Minmin; Liu, Haiping; Zhang, Huangang; Wang, Kairui; Zhang, Jinlian; Zhang, Zhongwei (Frontiers in Pharmacology, 2021)
Objective: The technology, network pharmacology and molecular docking technology of the ultra performance liquid chromatography-quadrupole time-of-flight tandem mass spectrometry (UPLC-Q-TOF-MS/MS) were used to explore the potential molecular mechanism of Platycodon grandiflorum (PG) in the treatment of lung cancer (LC). Methods: UPLC-Q-TOF-MS/MS technology was used to analyze the ingredients of PG and the potential LC targets were obtained from the Traditional Chinese Medicine Systems Pharmacology Database, and the Analysis Platform (TCMSP), GeneCards and other databases. The interaction network of the drug-disease targets was constructed with the additional use of STRING 11.0. The pathway enrichment analysis was carried out using Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) in Metascape, and then the “Drug-Ingredients-Targets-Pathways-Disease” (D-I-T-P-D) network was constructed using Cytoscape v3.7.1. Finally, the Discovery Studio 2016 (DS) software was used to evaluate the molecular docking. Results: Forty-seven compounds in PG, including triterpenoid saponins, steroidal saponins and flavonoids, were identified and 9 main bioactive components including platycodin D were screened. According to the method of data mining, 545 potential drug targets and 2664 disease-related targets were collected. The results of topological analysis revealed 20 core targets including caspase 3 (CASP3) and prostaglandin-endoperoxide synthase 2 (PTGS2) suggesting that the potential signaling pathway potentially involved in the treatment of LC included MAPK signaling pathway and P13K-AKT signaling pathway. The results of molecular docking proved that the bound of the ingredients with potential key targets was excellent. Conclusions: The results in this study provided a novel insight in the exploration of the mechanism of action of PG against LC.